An advanced phytoplankton trophic index: Test and validation with a nationwide lake survey in Poland. Issue 1 (April 2016) - Pasztaleniec, Agnieszka
Abstract : The use of phytoplankton as a tool to assess the status of ecosystems in monitoring programmes should consider its taxonomic composition [Water Framework Directive‐WFD, 2000/60/EC]. One of the approaches towards phytoplankton composition assessment in relation to eutrophication process is the use of phytoplankton trophic indices based on taxa preferences along a trophic gradient. Monitoring data on phytoplankton (biomass, taxonomic structure) and physicochemical parameters (total phosphorus, total nitrogen, Secchi Disc) from 366 lake‐years surveyed in 2008–2012 were used to develop the WFD‐compiled trophic index (TITP+TN ). Data from 104 lakes surveyed in 2013 served as a validation dataset. The TITP+TN was calculated based on the trophic optima of genera, calculated against both phosphorus and nitrogen concentrations for unstratified and stratified lakes separately. Statistical analysis showed a considerable number of relationships between the TITP+TN and eutrophication parameters (e.g., chlorophyll a concentration, cyanobacterial biomass). The results demonstrate the utility of the new phytoplankton trophic index for water‐quality assessment. Based on the frequency distribution of index scores, the boundary values for subsequent classes of ecological status were elaborated.